Synthesis of Some Phthalomido-oxy and Amino-oxy Derivatives of Benzotriazole - Banu, Tahira; Rajora, Sonal; Mehat, Depika; Talesera, G.L. (Asian Journal of Chemistry, 2010)
Some important N'-[(benzotriazol-1-yl) alkoxy] phthalimides (6a–c) were synthesized by condensation of phthalimido-oxy alkyl bromides with benzotriazole. These compounds on hydrolysis in acidic media were converted to corresponding amino-oxy compounds (7a–c).